PATTERNS OF TEACHER – STUDENTS’ INTERACTION IN EFL ZOOM MEETING CLASS IN SMP NEGERI 1 GANRATANG KEKE - Nurjannah; Abdul, Nurdevi Bte; Hamid, Sitti Maryam (FKIP Unismuh Makassar, 2023)
This study aims to reveal patterns of teacher – students among interaction student in an EFL class at SMP Negeri 1 Gantarang Keke public secondary school through zoom cloud meeting and to describe the teacher-students and student-student interaction patents in the EFL class. The method used in this research is descriptive qualitative method. The subject of this research was a teacher and students’ class VII of SMP Negeri 1 Gantarang Keke. The instruments used were observation and interviews. The results of this study indicate that the introduction patterns that emerge in the classroom are group work, individual choral responded, and collaboration. Teaching and learning conferences are not only frequent when teacher want to test their skills with quizzes, but they also have difficulty understanding the lesson, not only that they often go in and out when teacher want to test their abilities factors in Zoom meeting are supporting factor. That is, to support a face-to-face online learning process, albeit virtual, and inhibiting factor for the zoom meeting is internet quotas as most students complain about internet quota, internet network and time strains limited. The conclusion of this study indicate that teacher-students and student-student interaction patterns are not effective in EFL classes.